Springer handbook of computational intelligence - Janusz Kacprzyk (Springer, 2015)
This Springer Handbook of Computational Intelligence is a result of a broad project that has been launched by us to respond to an urgent need of a wide scientific and scholarly community for a comprehensive reference source on Computational Intelligence, a field of science that has for some decades enjoyed a growing popularity both in terms of the theory and methodology as well as numerous applications. As it is always the case in such situations, after some time once an area has reached maturity, and there is to some extent a consent in the community as to which paradigms, and tools and techniques may be useful and promising, the time will come when some state of the art exposition, exemplified by this Springer Handbook, would be welcome. We think that this is the right moment.